A network analysis of timing and conditions present at time of death for periviable infants (22+0–23+6 weeks) admitted to neonatal intensive care after receiving survival-focused care at birth - Peterson, J.; Smith, D. M.; Johnstone, E. D.; Harvey, K.; Mahaveer, A. (Frontiers in Pediatrics, 2025)
IntroductionAdvances in neonatal care have resulted in improved survival rates for periviable infants (22 + 0–23 + 6 weeks) with increasing numbers being admitted to neonatal intensive care units across the United Kingdom. Qualitative research evidences the conflict perinatal professionals experience traversing the line between providing life-sustaining treatment to these infants, whilst not wanting to inflict a prolonged period of suffering to infants who will ultimately die. Professionals currently lack adequate prognostic tools to accurately predict pre-birth which infants will survive.MethodsThis study utilises an anonymised dataset from the North West Neonatal Network to delineate time of death profiles for periviable infants admitted to neonatal intensive care units (NICU) and explores the demographics, timing and diagnoses recorded at the time of the death.ResultsThe data show that most periviable infants who died following admission to NICU died within the first seven days after birth [24 infants born at 22 weeks (65%) and 55 infants born at 23 weeks (52%)]. For infants born at 22 weeks who subsequently died on NICU, 89% had died within 14 days after birth. Reorientation of care was recorded as a relevant factor at the time of death in a minority of patients [23 infants (16%)].DiscussionWhere active, survival-focused care has been initiated, the response of the infant to intensive care and the likelihood of their survival emerges over a relatively short timeframe after admission. This lends support to a trial of therapy approach for suitable periviable infants balancing the need to avoid iatrogenic harm to infants who will ultimately die despite intensive care, whilst not denying them the chance at survival. Management of periviable deliveries requires coordinated parallel planning and a high-quality palliative care approach throughout.